2018
DOI: 10.1038/s41434-018-0043-6
|View full text |Cite|
|
Sign up to set email alerts
|

Epistasis between Pax6Sey and genetic background reinforces the value of defined hybrid mouse models for therapeutic trials

Abstract: The small eye (Sey) mouse is a model of PAX6-aniridia syndrome (aniridia). Aniridia, a congenital ocular disorder caused by heterozygous loss-of-function mutations in PAX6, needs new vision saving therapies. However, high phenotypic variability in Sey mice makes development of such therapies challenging. We hypothesize that genetic background is a major source of undesirable variability in Sey mice. Here we performed a systematic quantitative examination of anatomical, histological, and molecular phenotypes on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…The lens is very sensitive to Pax6 dosage as heterozygous germ line mutations in mice result in the “small eye ( Sey) ” phenotype ( Hill et al, 1991 ), which is characterized by congenital reductions in eye size driven by reductions in lens size ( Bassnett and Šikić, 2017 ; Collinson et al, 2001 ; Voskresenskaya et al, 2021 ), the extent of which is highly dependent on genetic backgrounds ( Hickmott et al, 2018 ). In some cases these mice exhibit congenital cataracts ( Gregory-Evans et al, 2014 ), in others, Sey mice develop cataracts by middle age with some reports finding a prevalence of anterior subcapsular cataracts due to the fibrotic transition of the lens epithelium ( Duncan et al, 2000 ; Lovicu et al, 2004 ) and cortical opacities driven by lens fiber cell abnormalities ( Duncan et al, 2000 ).…”
Section: Vertebrate Eye Organogenesis: Focus On the Function Of ...mentioning
confidence: 99%
“…The lens is very sensitive to Pax6 dosage as heterozygous germ line mutations in mice result in the “small eye ( Sey) ” phenotype ( Hill et al, 1991 ), which is characterized by congenital reductions in eye size driven by reductions in lens size ( Bassnett and Šikić, 2017 ; Collinson et al, 2001 ; Voskresenskaya et al, 2021 ), the extent of which is highly dependent on genetic backgrounds ( Hickmott et al, 2018 ). In some cases these mice exhibit congenital cataracts ( Gregory-Evans et al, 2014 ), in others, Sey mice develop cataracts by middle age with some reports finding a prevalence of anterior subcapsular cataracts due to the fibrotic transition of the lens epithelium ( Duncan et al, 2000 ; Lovicu et al, 2004 ) and cortical opacities driven by lens fiber cell abnormalities ( Duncan et al, 2000 ).…”
Section: Vertebrate Eye Organogenesis: Focus On the Function Of ...mentioning
confidence: 99%
“…Instead, it was found that the microphthalmia phenotype (in Le-Cre homozygous mice) was caused by changes in the expression of genes involved in the negative regulation of cell proliferation and cell growth, and positive regulation of apoptosis pathways. Since these two studies used mice of different strains, the disagreement between them may be explained by strain-dependent differences in Pax6 expression [48] and/or susceptibility to eye development phenotypes when exposed to changes in Pax6 expression or PAX6 levels [48, 49]. Regardless of its cause, it is critical that any study utilizing the Le-Cre transgene control for the effect of the Le-Cre alone.…”
Section: Discussionmentioning
confidence: 99%
“…We used an earlier in vitro-optimized CRISPR strategy (Figure 3A) to insert a 3xFLAG tag to the Sey allele in mouse zygotes in a rapid manner, creating the 3xFLAG-tagged Sey mouse strain (C57BL/6J [B6]-Pax6 Sey-em1(3xFLAG)Ems ), called Fey hereafter. Since the Sey mutation causes a premature stop codon and no detectable protein, 39 we were unable to directly characterize the function of the Fey allele. Thus, we created the matched WT control strain (B6-Pax6 em3(3xFLAG)Ems ), called Fax hereafter.…”
Section: An Optimized Crispr Strategy Successfully Inserted 3xflag Tag In Mouse Embryonic Stem Cellsmentioning
confidence: 99%
“…Protein extraction, quantification, and western blotting were performed according to a previously described protocol. 39 Briefly, E18.5 brain hemispheres were homogenized in lysis buffer. The extracted proteins were quantified and 34 mg of each protein sample was run on the gel before being transferred to the polyvinylidene fluoride (PVDF) membrane.…”
Section: Western Blot Analysismentioning
confidence: 99%